Inferring graph grammars by detecting overlap in frequent subgraphs - Kukluk, Jacek P.; Holder, Lawrence B.; Cook, Diane J. (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we study the inference of node and edge replacement graph grammars. We search for frequent subgraphs and then check for an overlap among the instances of the subgraphs in the input graph. If the subgraphs overlap by one node, we propose a node replacement graph grammar production. If the subgraphs overlap by two nodes or two nodes and an edge, we propose an edge replacement graph grammar production.
Keywords: grammar induction; graph grammars; graph mining; multi-relational data mining